Eumenitin, a novel antimicrobial peptide from the venom of the solitary eumenine wasp Eumenes rubronotatus - Konno, Katsuhiro; Hisada, Miki; Naoki, Hideo; Itagaki, Yasuhiro; Fontana, Renato; Rangel, Marisa; Stolarz Oliveira, Joacir; Perez dos Santos Cabreraf, Marcia; Ruggiero Neto, Joao; Hide, Izumi; Nakata, Yoshihiro; Yasuhara, Tadashi; et al. (Elsevier B.V., 2006)
A novel antimicrobial peptide, eumenitin, was isolated from the venom of the solitary eumenine wasp Eumenes rubronotatus. The sequence of eumenitin, Leu-Asn-Leu-Lys-Gly-Ile-Phe-Lys-Lys-Val-Ala-Ser-Leu-Leu-Thr, was mostly analyzed by mass spectrometry together with Edman degradation, and corroborated by solid-phase synthesis. This peptide has characteristic features of cationic linear a-helical antimicrobial peptides, and therefore, can be predicted to adopt an amphipathic a-helix secondary structure. In fact, the CD spectra of eumenitin in the presence of TFE or SDS showed a high content of alpha-helical conformation. Eumenitin exhibited inhibitory activity against both Gram-positive and Gram-negative bacteria, and moderately stimulated degranulation from the rat peritoneal mast cells and the RBL-2H3 cells, but showed no hemolytic activity against human erythrocytes. This antimicrobial peptide in the eumenine wasp venom may play a role in preventing potential infection by microorganisms during prey consumption by their larvae. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: eumenitin; solitary wasp venom; antimicrobial peptide; cationic linear alpha-helical peptide; amphipathic alpha-helix structure